2010
DOI: 10.1299/jtst.5.200
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Correlation for 2,3,3,3-Tetrafluoropropene (HFO-1234yf) Based on the Extended Corresponding States Model

Abstract: The viscosity of 2,3,3,3-tetrafluoropropene (HFO-1234yf) has been successfully correlated with the extended corresponding states (ECS) model for transport properties. The thermodynamic equation of state developed in our earlier work forms the basis of this work. The viscosity correlation presented here is valid for temperatures from 260 K to 340 K and for pressures up to 20 MPa. The correlation can be applied to both liquid and gas phases in a single procedure. The estimated uncertainties are 2 % for liquid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Apart from the viscosity correlations used in REFPROP there are others viscosity models available in the literature for R-1234yf and for R-1234ze(E) which, however, are not discussed here.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Apart from the viscosity correlations used in REFPROP there are others viscosity models available in the literature for R-1234yf and for R-1234ze(E) which, however, are not discussed here.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As a very promising alternative refrigerant, R1234yf attracts more and more attention with zero ODP (ozone depletion potential) and a 100-year GWP (global warming potential) lower than 1. The heat transfer performance, saturated vapor pressure, and viscosity of R1234yf have been reported, but the research on the potential applications in absorption refrigeration systems has not been reported. As absorbents DMETrEG (triethylene glycol dimethyl ether) and NMP have a high boiling point, weak toxicity, and good ability to dissolve many refrigerants, such as R134a, R161, and R32.…”
Section: Introductionmentioning
confidence: 99%
“…However, there currently are few wide-ranging correlations for the viscosity of R1234yf or R1234ze(E). There is one extended corresponding states (ECS) model for the viscosity of R1234yf (Akasaka, 2010) and unpublished ECS models for both R1234yf and R1234ze(E) in REFPROP (Lemmon et al, 2013), and most recently a free-volume based model (He et al, 2015). In this work we develop correlations for the viscosity as a function of temperature and density that are valid over a wide range of fluid states including gas, liquid, and supercritical regions for R1234yf and R1234ze(E) and compare with known experimental data.…”
Section: Introductionmentioning
confidence: 99%